The Students’ Perception of the Use of ChatGPT as a Vocabulary Learning Medium: A Case Study of Second-Semester Students at the English Department University of Mataram - Isnaini, Zohratul; Susanti, Ni Wayan Mira; Putera, Lalu Jaswadi (Journal of Authentic Research, 2025)
This study explored second-semester students’ perceptions of using ChatGPT as a vocabulary learning tool at the University of Mataram. Using a qualitative method through questionnaires and semi-structured interviews, data were collected from 92 students, with 15 selected for interviews. The findings showed that most students had positive perceptions of ChatGPT, citing its usefulness in understanding word meanings, receiving instant feedback, and enabling flexible, independent learning. However, challenges such as long or unclear explanations and limited internet access were reported. The most common issue was difficulty understanding complex responses (46.74%), while the least was lack of motivation (7.61%). Despite these issues, students showed strong interest in continuing to use ChatGPT. The study concluded that ChatGPT supports vocabulary acquisition but should be guided and adapted to learners’ needs.